2017
DOI: 10.1111/and.12878
|View full text |Cite
|
Sign up to set email alerts
|

Pathological changes in Sertoli cells and dysregulation of divalent metal transporter 1 with iron responsive element in the testes of idiopathic azoospermia patients

Abstract: Iron is essential for rapidly dividing spermatocytes during normal mammalian spermatogenesis. Decreased transferrin and transferrin receptor levels were observed in seminal plasma from idiopathic azoospermia (IA) patients, suggesting disturbed iron metabolism in IA testes. However, how Sertoli cells (SCs) contribute to the iron homoeostasis in IA is still unclear. In this study, we analysed 30 IA and 30 age-matched obstructive azoospermia (OA) patients undergoing testicular sperm aspiration (TESA). SCs hyperpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…In the present study, we observed that WYP promoted SC viability in a dose‐dependent manner. Often, Ki67 is used to label SC proliferation (Jing et al., 2018), in the present study, the 43°C heat stress decreased Ki67 expression; conversely, WYP administration ameliorated the downregulation of Ki67 in SCs. Therefore, according to the result of this study, WYP enhanced SC viability and proliferation.…”
Section: Discussionsupporting
confidence: 56%
“…In the present study, we observed that WYP promoted SC viability in a dose‐dependent manner. Often, Ki67 is used to label SC proliferation (Jing et al., 2018), in the present study, the 43°C heat stress decreased Ki67 expression; conversely, WYP administration ameliorated the downregulation of Ki67 in SCs. Therefore, according to the result of this study, WYP enhanced SC viability and proliferation.…”
Section: Discussionsupporting
confidence: 56%
“…Iron oxide nanoparticles (NPs) are commonly utilized for biomedical applications and have been reported to easily pass through the BTB and enter the testis, causing iron accumulation and testicular tissue damage, thereby resulting in oxidative stress [71]. At the same time, decreased Tf and TfR levels have been observed in the seminal plasma from idiopathic azoospermia (IA) patients, which can also be attributed to the upregulation of IRP1 and HIF-1α, leading to dysregulation of DMT1+IRE in the IA testis [72]. The pituitary gland, on the other hand, is particularly sensitive to iron, and iron overload can also lead to severe impairment of the hypothalamus/pituitary/gonadal axis, thus causing hypogonadism and low testosterone levels [73].…”
Section: Reduced Testosterone Levels Caused By Iron Overload In the T...mentioning
confidence: 99%
“…It was recently observed that low sperm quality and sperm necrosis positively correlated with iron metabolism indices (ferritin, iron, transferrin evaluated in seminal plasma) in individuals with leukocytospermia and varicocele, both of which are characterized by the presence of inflammatory status and OS condition [53]. Altered iron metabolism is involved in ROS production [54][55][56][57] and drives chronic inflammation affecting male fertility [58,59]. Interestingly, several studies reported that ferroptosis, an iron-dependent programmed cell death, can affect spermatogenetic process leading to male infertility [60,61].…”
Section: Male Infertility and Oxidative Stressmentioning
confidence: 99%